Stable pulmonary function after haploidentical stem cell transplantation with post-transplant cyclophosphamide: a single center experience. Issue 2 (28th January 2022) - Paviglianiti, Annalisa; Sestili, Simona; Bianchessi, Antonio; Memoli, Mara; Dulery, Remy; Banet, Anne; Van De Wyngaert, Zoe; Belhocine, Ramdane; Ledraa, Tounes; Malard, Florent; Mohty, Mohamad; Brissot, Eolia
Abstract: Prior studies have reported pulmonary function tests (PFT) before and after related and unrelated allogeneic hematopoietic stem cell transplantation (HSCT). However, limited data exist on the evaluation of lung function after haploidentical stem cell transplantation (HAPLO) with post-transplant cyclophosphamide (PTCY). We retrospectively reported the evaluation of PFTs at screening before HAPLO in 80 patients at 100 days and 1 year of follow-up. The proportion of surviving patients with available PFTs at 100 days and 1 year were 86% and 68%, respectively. During the follow-up period, four patients met the criteria for bronchiolitis obliterans syndrome and two for interstitial lung disease. Overall survival was 73% (95% CI 62–82%) at 2 years. We observed a significant reduction in diffusing capacity of the lungs for carbon monoxide (DLCO) corrected for the most recent hemoglobin concentration (DLCOc) at 100 days after HAPLO. However, an overall substantial stable pulmonary function was observed at 1 year.